Village Information Delivery through Suara Waditra Community Radio amidst Digital Media Challenges - Sjuchro, Dian Wardiana; Bakti, Iriana; Rahmat, Agus; Sjafirah, Nuryah Asri; Nurfauziah, Isni (Jurnal Communio : Jurnal Jurusan Ilmu Komunikasi, 2025)
Community radio is one form of broadcasting institution that is legal and exists in Indonesia based on Law No. 32 of 2002 on Broadcasting. Community radios are created by and for the benefit of the communities they serve. One of the community radios that currently still exists in broadcasting is Suara Waditra Community Radio, which is used by the local village government as a medium for delivering information about the countryside. This research aims to find out the extent of the communication strategy of the Sukasetia Village Government in terms of delivering information to residents. This research is descriptive qualitative research with a case study approach. Data was collected through observation and in-depth interviews with selected informants. The results showed that the Village Government's communication strategy through radio broadcasting on Suara Waditra Community Radio was quite good. Through the Village Corner segment, the Village Government conveys information about the countryside that can be accessed easily and cheaply by residents. The village corner segment is welcomed by residents, as evidenced by statements from villagers that the information delivered on Community Radio is especially useful. However, the integration of Community Radio and digital media should still be done to support the delivery of faster and more comprehensive information.